2016
DOI: 10.1038/srep23665
|View full text |Cite
|
Sign up to set email alerts
|

Metformin stimulates IGFBP-2 gene expression through PPARalpha in diabetic states

Abstract: The anti-diabetic drug, metformin, exerts its action through AMP-activated protein kinase (AMPK), and Sirtuin (Sirt1) signaling. Insulin-like growth factor (IGF)-binding protein 2 (IGFBP-2) prevents IGF-1 binding to its receptors, thereby contributing to modulate insulin sensitivity. In this study, we demonstrate that metformin upregulates Igfbp-2 expression through the AMPK-Sirt1-PPARα cascade pathway. In the liver of high fat diet, ob/ob, and db/db mice, Igfbp-2 expression was significantly decreased compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 42 publications
4
33
0
Order By: Relevance
“…Mouse primary hepatocytes were isolated from WT and Pparα -null mice as described previously 24 . Briefly, isolated primary hepatocytes were cultured in Dulbecco’s modified Eagle’s medium (DMEM; Invitrogen, Carlsbad, CA, USA) containing 10% heat-inactivated FBS, 100 units/ml penicillin G, 100 μg/ml streptomycin, 10 μM dexamethasone, 100 nM insulin, and 25 mM glucose.…”
Section: Methodsmentioning
confidence: 99%
“…Mouse primary hepatocytes were isolated from WT and Pparα -null mice as described previously 24 . Briefly, isolated primary hepatocytes were cultured in Dulbecco’s modified Eagle’s medium (DMEM; Invitrogen, Carlsbad, CA, USA) containing 10% heat-inactivated FBS, 100 units/ml penicillin G, 100 μg/ml streptomycin, 10 μM dexamethasone, 100 nM insulin, and 25 mM glucose.…”
Section: Methodsmentioning
confidence: 99%
“…The PPARα response element (PPRE) was identified on a mouse IGFBP-2 promoter, indicating that IGFBP-2 is a direct target of PPARα. Moreover, mRNA expression of the IGFBP-2 gene is activated by metformin, which is an antidiabetic drug for patients with diabetes and obesity, and the serum level of IGFBP-2 is stimulated in metformin-challenged diabetic patients [10]. A recent study in humans suggested that the circulating concentration of IGFBP-2 is associated with metabolic syndrome, including insulin resistance and obesity [1112].…”
Section: Transcriptional Regulation Of Igfbp-2mentioning
confidence: 99%
“…Production of IGFBP-2 is decreased in obese people compared with nonobese individuals, and concentrations of serum IGFBP-2 decrease with increasing body mass index [13]. Several reports have demonstrated that circulating IGFBP-2 concentrations are lower in patients with type 2 diabetes mellitus or obesity [1031]. Because overexpression of IGFBP-2 leads to recovered blood glucose levels in diabetic animal models, and because the antidiabetic drug, metformin, can recover serum IGFBP-2 levels in diabetic patients [10], decreased IGFBP-2 levels may lead to the development of diabetes in humans.…”
Section: Clinical Relevance Of Igfbp-2 Levels In Human Serummentioning
confidence: 99%
See 1 more Smart Citation
“…PPARα, a molecular target of resveratrol [39], participates in the promotion of adipocyte differentiation, the modulation of nutritional metabolism, and the inhibition of in ammatory response [40,41]. Previous study showed that resveratrol increased the levels of sirtuin-1 (SIRT1) and PPARα to mediate its protective effect on hypertension under maternal high-fat diet in the kidneys of male progeny [42].…”
Section: Discussionmentioning
confidence: 99%